Defining Eligibility of FOLFIRINOX for First-Line Metastatic Pancreatic Adenocarcinoma (MPC) in the Province of British Columbia: A Population-based Retrospective Study. (December 2017) - Ho, Maria Yi; Kennecke, Hagen F.; Renouf, Daniel J.; Cheung, Winson Y.; Lim, Howard J.; Gill, Sharlene
Abstract : Background: FOLFIRINOX is a first-line treatment option for patients with metastatic pancreatic cancer (MPC) and is associated with improved survival yet significantly more toxicities than standard gemcitabine. Our aim was to determine the proportion of patients with MPC who would be eligible for FOLFIRINOX based upon the pivotal ACCORD study criteria. Methods: Patients with confirmed MPC at the time of referral to the BC Cancer Agency between 2004 and 2007 were identified from the Gastrointestinal Cancers Outcomes Unit Database (GICOU). Proportion of patients that met the ACCORD study eligibility criteria was determined by chart review. Criteria for FOLFIRINOX exclusion were assessed using descriptive statistics. Results: A total of 100 consecutive patients with complete chart records and MPC were identified. Fifty-two (52%) were male and the median age was 68 years (range, 42 to 98 y). The most common sites of metastases were liver (63%) and peritoneum (22%). Only 26 patients fulfilled the ACCORD study eligibility criteria. The most common reasons for FOLIFIRINOX exclusion per ACCORD were poor Eastern Cooperative Oncology Group score of ≥2 (64%), age of 76 years or greater (22%), elevated bilirubin (22%), and inadequate renal function (6%). Conclusions: Despite the proven survival benefit of FOLFIRINOX, only approximately one quarter of patients in the real-world setting with MPC would have been considered eligible for such therapy based upon the ACCORD eligibility criteria. Careful patient selection and more tolerable therapies are required.